Physiological significance of isoprenoids and phenylpropanoids in drought response of Arundinoideae species with contrasting habitats and metabolism. (26th July 2016) - Velikova, Violeta; Brunetti, Cecilia; Tattini, Massimiliano; Doneva, Dilyana; Ahrar, Mastaneh; Tsonev, Tsonko; Stefanova, Miroslava; Ganeva, Tsveta; Gori, Antonella; Ferrini, Francesco; Varotto, Claudio; Loreto, Francesco
Abstract: Physiological, biochemical and morpho‐anatomical traits that determine the phenotypic plasticity of plants under drought were tested in two Arundinoideae with contrasting habitats, growth traits and metabolism: the fast‐growing Arundo donax, which also is a strong isoprene emitter, and the slow‐growing Hakonechloa macra that does not invest on isoprene biosynthesis. In control conditions, A . donax displayed not only higher photosynthesis but also higher concentration of carotenoids and lower phenylpropanoid content than H . macra . In drought‐stressed plants, photosynthesis was similarly inhibited in both species, but substantially recovered only in A . donax after rewatering. Decline of photochemical and biochemical parameters, increased concentration of CO2 inside leaves, and impairment of chloroplast ultrastructure were only observed in H . macra indicating damage of photosynthetic machinery under drought. It is suggested that volatile and non‐volatile isoprenoids produced by A . donax efficiently preserve the chloroplasts from transient drought damage, while H . macra invests on phenylpropanoids that are less efficient in preserving photosynthesis but likely offer better antioxidant protection under prolonged stress. Abstract : There is increasing interest in understanding the occurrence and importance of functional and structural traits, which determine plant plasticity under global change scenarios. In the present study, functional, metabolic and structural evidences are presented explaining why Arundo donax is a species more resistant to drought and has a better plasticity than other Arundinoideae. Our analyses demonstrate that volatile and non‐volatile isoprenoids produced by A . donax efficiently preserve the chloroplasts from transient drought damage, while Hakonechloa macra invests on phenylpropanoids that are less efficient in preserving photosynthesis but likely offer better antioxidant protection under prolonged stress.